2013
DOI: 10.4049/jimmunol.1301110
|View full text |Cite
|
Sign up to set email alerts
|

Parasite Infections in Multiple Sclerosis Modulate Immune Responses through a Retinoic Acid–Dependent Pathway

Abstract: We recently demonstrated better outcomes in helminth-infected multiple sclerosis (MS) patients, compared with uninfected ones. The present study evaluates the role of TLR2 and retinoic acid (RA) in parasite-driven protection in MS patients. RA serum levels were significantly higher in helminth-infected MS patients than in uninfected MS subjects or healthy controls. Genes involved in RA biosynthesis and metabolism, such as Adh1 and Raldh2, as well as RA receptors and IL-10, were induced in dendritic cells (DCs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
35
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 55 publications
0
35
0
Order By: Relevance
“…The role of TLR2 signaling in MS patients, however, is controversial. Helminth-infected MS patients were found to have TLR2-dependent programming of dendritic cells that induced regulatory T cells (Tregs), suppressed production of proinflammatory cytokines, and was associated with upregulation of genes involved in retinoic acid biosynthesis and metabolism (4). In contrast, Nyirenda et al (5) reported that TLR2 activation is involved in the reduced Treg function reported in MS.…”
mentioning
confidence: 91%
“…The role of TLR2 signaling in MS patients, however, is controversial. Helminth-infected MS patients were found to have TLR2-dependent programming of dendritic cells that induced regulatory T cells (Tregs), suppressed production of proinflammatory cytokines, and was associated with upregulation of genes involved in retinoic acid biosynthesis and metabolism (4). In contrast, Nyirenda et al (5) reported that TLR2 activation is involved in the reduced Treg function reported in MS.…”
mentioning
confidence: 91%
“…Without this developmental and epigenetic programming, the helminths might not be necessary or even effective. The recent failure of trials attempting to treat IBD with Trichuris suis in Americans or Europeans (http://tinyurl.com/nodazuu) is disappointing, and should alert us to this possibility, though it is also possible that the repeated dosing required when using this organism, which cannot establish itself in the human gut, eventually drives immunity rather than the systemic immunoregulation seen with natural human infections that become established and tolerated (Correale and Farez, 2013).…”
Section: Genetics Epigenetics and Future Therapiesmentioning
confidence: 99%
“…For example, blood nematodes are powerfully immunoregulatory, and relatively harmless if tolerated, but aggressive immune responses that attempt (unsuccessfully) to eliminate them destroy the lymphatic system and result in elephantiasis (Babu et al, 2006). Immunoregulation by these three categories of organisms (Old infections, microbiotas and organisms from the natural environment), collectively known as the "Old Friends" has been reviewed in detail elsewhere (Rook, 2010;Rook et al, 2013), but briefly, they can be shown to block or treat a wide range of chronic inflammatory disorders in animal models (Osada and Kanazawa, 2010), and although many more mechanisms remain to be revealed, many of them secrete molecules that expand regulatory T cell (Treg) populations (Atarashi et al, 2011;Grainger et al, 2010;Round et al, 2011), or cause dendritic cells to drive Treg rather than inflammatory effector cells (Correale and Farez, 2013;Smits et al, 2005). The latter "Treg adjuvant" function might explain the observation that patients with early relapsing/remitting multiple sclerosis (MS) who picked up helminth infections were found to develop circulating populations of Treg specific for myelin basic protein that coincided with a halt in disease progression (Correale and Farez, 2007).…”
mentioning
confidence: 99%
“…Retinoic acid concentrations are higher in MS patients infected by helminthes comparing to healthy individuals (Correale and Farez 2013).…”
Section: Multiple Sclerosismentioning
confidence: 99%